Educating the Principles of Judiciary in Eastern Europe - Treskov, Aleksej P. (2020)
The study subject in this article is aims to educate the concepts of judiciary principles in Eastern eroup. We substantiated the conclusion on constitutional structuring of the formalization of judiciary principles in the sections devoted to the state foundations (constitutional system); human and civil rights and freedoms; judiciary; higher judicial authorities (usually the constitutional court). A comparative legal study of the norms of special sections on judiciary contained in the constitutions of Eastern European countries allowed the author forming a list of principles that organize and constitute the basis of activity of this kind of judiciary; identify the specific nature of their consolidation; present quantitative and qualitative features of the declared fundamental principles.